Implementasi PP Nomor 37 Tahun 1998 tentang Peraturan Jabatan PPAT dan PMA, serta Peraturan Kepala BPN Nomor 33 Tahun 2021 tentang Uang Jasa PPAT terhadap Penetapan Uang Jasa PPAT di Kota Padang - Putra Aulia Rahman; Yuslim; Charles Simabura; Annisa’ Suryani Oktapia (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
PPAT is a public official with duties, authorities, obligations, and rights, one of which is the right to service fees. This right was originally regulated in Article 32 paragraph (1) of Government Regulation No. 37 of 1998, which states that PPAT is entitled to request a service fee of a maximum of 1%. However, the Minister of ATR/Head of BPN Regulation No. 33 of 2021 provides a tiered arrangement: up to Rp500,000,000 at a maximum of 1%, Rp500,000,000–Rp1,000,000,000 at a maximum of 0.75%, Rp1,000,000,000–Rp2,500,000,000 at a maximum of 0.5%, and above Rp2,500,000,000 at a maximum of 0.25%. These two regulations show a significant difference in the regulatory framework. The research problems are: (1) the implementation of PPAT service fees in Padang City, and (2) the legal certainty between the two regulations. The theories employed are the theory of legal certainty and the theory of legislation formation. This research is socio-legal research with a descriptive-analytical approach, using a sample of 10 PPATs in Padang City through interviews and document studies, then analyzed qualitatively. The results show that the implementation of PPAT service fee determination in Padang City is still varied and does not fully reflect the maximum limits set forth in the applicable regulations. Normatively, this condition indicates a disharmony between the maximum service fee limits, which has an impact on differences in field implementation. These empirical findings confirm the need for regulatory review to strengthen clarity, consistency of application, and legal certainty for both the public and PPATs